Developmental Trajectory of Inattention and Its Association With Depressive Symptoms in Adolescence: Peer Relationships as a Mediator - Park, Sohee; Chang, Hyein (Frontiers in Psychology, 2022)
This study investigated the developmental trajectory of inattention symptoms as a predictor of later depression in adolescence, and examined potential mediating role of peer relationship in this process. Participants were adolescents who were part of the large longitudinal panel study on Korean Youths(KCYPS) of the National Youth Policy Institute(NYPI). Specifically, data were drawn from two cohorts of KCYPS that differed in participant age(Panel 1: 2003 birth cohort, n=2342, 48.2% girls; Panel 2: 2000 birth cohorts, n=2378, 40.0%girls). We analyzed data collected from 2010 to 2016 when children in panel 1 were 6-7 to 12-13 years old, and children in panel 2 were 9-10 to 15-16 years old. Results of latent growth modeling were as follows. In Panel 1, the inattention symptoms increased from 9-10 to 12-13 years . Otherwise, the inattention symptoms decreased from 11-12 to 15-16 years in panel 2. Additionally, in both panels, initial status and slope of inattention significantly predicted later levels of depression symptoms, and peer relationship partly mediated the association between inattention trajectory and depression. The findings are discussed with respect to considering the growth of inattention and the quality of peer relationship as promising targets for early identification and intervention of depression in adolescents.